The future of protein sources in livestock feeds: implications for sustainability and food safety - Pexas, Georgios; Doherty, Bob; Kyriazakis, Ilias (Frontiers in Sustainable Food Systems, 2023)
The feed-food competition for environmental and economic resources raises increasing concerns about the production and supply of protein for the global livestock sector. Risks to food-security and approaching deadlines for global sustainable development, means exploring alternative protein feed ingredients is imperative. This Review discusses the potential for soilless, local and circular protein feed sources to provide solutions for key sustainability and food-security threats to the global livestock sector, through their partial incorporation in future livestock feeds and feeding systems. In doing so, it offers a holistic insight into the potential opportunities, but also risks associated with such alternatives.Through this analysis, a four-point strategic plan is synthesised to facilitate higher-level policy making that may enable implementation of these alternative ingredients at commercial scales, building towards a more sustainable and resilient livestock industry.